O sertão imaginado nas Bachianas Brasileiras de Heitor Villa-Lobos - Medeiros, Ana Judite de Oliveira (2020)
Considering the influence of popular and folk music in the Bachianas Brasileiras Series by Heitor Villa-Lobos (1887-1959), the thesis brings a reflective perspective on the northeastern Sertão. The Bachianas Series is a musical work, which in its structure, refers to the music Johann Sebastian Bach (1685-1750), therefore ‘bachianas’. In it, each suite merges in its own way with Brazilian folk and popular music, especially the Choro style and country music (NÓBREGA, 1971; KIEFER, 1997; CALDAS, 2010). For the research, four pieces of the Series were examined: Introduction Embolada, Dance Lembrança do Sertão, Choir Canto do Sertão and Aria Cantiga, called Bachianas Sertanejas. From them, we investigated the historical and cultural influence (HOLANDA, 1982; ORTIZ, 2006; ALBUQUERQUE, 2011), which led the composer to insert rhythms and melodies characteristic of the region, such as Baião and the popular song “Ó mana deix’eu ir…”, in order to understand his imaginary elaboration of the region. And, considering the problem of northeasternity and regionality (ANDRADE, 1989; CASCUDO, 2000) present in the work, the research was developed under the approaches of language itself, as language of things and man (BENJAMIM, 2011) and exercise sociological (MILLS, 1996), to ‘look’ or ‘listen’ to a musical work and its possibilities and social connections. And also, from a musicological perspective, which considers how external characteristics are internalized and acquire other meanings in the interpretation, either as it leads or as it transforms (KERMAN, 2011; LOPES, 2014). Thus, the pieces of the Bachianas Brasileiras Series were analyzed in order to raise reflections on another look at the region through musical language.